Optimized design of high power density EMI filters for power electronic converters - Ala, G.; Giaconia, G.C.; Giglia, G.; Di Piazza, M.C.; Luna, M.; Vitale, G.; Zanchetta, Pericle (2016)
Nowadays, power density of power converters and related EMI filters is gaining more and more attention. This severely impacts on the design constraints in several application domains. A conventional design of the EMI filter does not guarantee the selection of components/configuration leading to the best power density. For this reason, an optimized design procedure of discrete EMI filters in terms of power density is proposed in this paper. It is based on a previously developed rule-based design procedure, introducing here additional features to obtain a more effective optimization of EMI filter's power density. The proposed approach has been validated in terms of EMI filter's performance and size reduction, by a comparison between an EMI filter designed using the optimized procedure and a conventionally designed one, for two different case studies.